Pulmonary Embolism After Acute Spinal Cord Injury and COVID-19. (November 2020) - Pisano, Thomas John; Joki, Jaclyn; Hon, Beverly; Cuccurullo, Sara
Abstract : Abstract: The coronavirus virus disease 2019 is best known for its pulmonary sequelae. Understanding of the disease process is rapidly growing, and the medical community already appreciates a hypercoagulable state associated with coronavirus virus disease 2019. Acute spinal cord injury has an inherent increased risk for venous thromboembolism. In this case report, the patient presented with bilateral lower limb weakness and sensory loss secondary to thoracic disc herniation. Incidentally, at the same time as the initial presentation, the patient was also found to have coronavirus virus disease 2019 without significant respiratory symptoms. During hospitalization, the patient developed extensive bilateral lower limb deep vein thrombosis despite chemoprophylaxis. Therapeutic anticoagulation was initiated, yet several days later, he developed pleuritic chest pain. Computed tomography angiography revealed bilateral pulmonary emboli. This case highlights the need for clinicians to have elevated vigilance with regard to screening and treatment for venous thromboembolism in high-risk patients, such as spinal cord injury with a concurrent diagnosis of coronavirus virus disease 2019. Abstract : Supplemental digital content is available in the text.